2022
DOI: 10.1002/cpt.2527
|View full text |Cite
|
Sign up to set email alerts
|

SLCO1B1*5 Allele Is Associated With Atorvastatin Discontinuation and Adverse Muscle Symptoms in the Context of Routine Care

Abstract: The SLCO1B1 genotype is known to influence patient adherence to statin therapy, in part by increasing the risk for statin-associated musculoskeletal symptoms (SAMSs). The SLCO1B1*5 allele has previously been associated with simvastatin discontinuation and SAMSs. Prior analyses of the relationship between SLCO1B1*5 and atorvastatin muscle side effects have been inconclusive due to insufficient power. We now quantify the impact of SLCO1B1*5 on atorvastatin discontinuation and SAMSs in a large observational cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…In the former study, 90% of the patients were using 80 mg/day atorvastatin, which is a substantially higher proportion than in our study and may partly explain the differing results. Nevertheless, the non-significant HR of 1.25 to 1.3 for the statin switch + CK measurement phenotype in C-allele carriers in our study is close to the odds ratio of 1.44 for atorvastatin intolerance and HR of 1.4 for atorvastatin-associated muscle symptoms in the previous studies [11–13,17,35].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the former study, 90% of the patients were using 80 mg/day atorvastatin, which is a substantially higher proportion than in our study and may partly explain the differing results. Nevertheless, the non-significant HR of 1.25 to 1.3 for the statin switch + CK measurement phenotype in C-allele carriers in our study is close to the odds ratio of 1.44 for atorvastatin intolerance and HR of 1.4 for atorvastatin-associated muscle symptoms in the previous studies [11–13,17,35].…”
Section: Discussionsupporting
confidence: 87%
“…Simvastatin acid is among the most sensitive drugs to alterations in SLCO1B1 genotype [5,6,[12][13][14]. Moreover, SLCO1B1 c.521T>C has been consistently associated with simvastatin and atorvastatin-induced myopathy and intolerance, especially when high doses are used [5,7,[12][13][14][15][16][17]. Although the pharmacokinetic effects are clear, the clinical evidence linking genetic variants in other pharmacokinetic genes as well as statins other than simvastatin and atorvastatin with statin intolerance is sparse.…”
Section: Introductionmentioning
confidence: 99%
“…11 The SLCO1B1 c.521T>C (rs4149056) single nucleotide variation (SNV) causes nearly total loss of OATP1B1 function and raises systemic exposure to atorvastatin and risk of musculoskeletal symptoms. 4,11,20 UGT1A3*2 increases UGT1A3 expression and lactonization of atorvastatin. 21 It has also been suggested that genetic variation of P-gp and BCRP may affect the pharmacokinetics of atorvastatin.…”
Section: Articlementioning
confidence: 98%
“…1 Musculoskeletal symptoms are a common reason for atorvastatin discontinuation, and increased atorvastatin exposure caused by drug-drug interactions or genetic variation raises the risk. [2][3][4] Atorvastatin is extensively metabolized to active 2-hydroxy atorvastatin and inactive metabolites, which are eliminated through bile. 5,6 Cytochrome P450 (CYP) 3A enzymes catalyze the hydroxylation of atorvastatin and its metabolites, with minor contribution from CYP2C8.…”
Section: Articlementioning
confidence: 99%
“…First identified through a genomewide association study of myopathy in patients treated with simvastatin 80 mg, 64 the reduced function haplotype (*5) has since been extended to other SAMS phenotypes 65 and statins 66 . Beyond symptoms, the *5 variant has also been associated with premature statin discontinuation for simvastatin 67 and atorvastatin 68 . Importantly, SAMS risk (in *5 allele carriers) appears to be a class effect pharmacokinetically, although the strength of association is statin type‐ and dose‐dependent 65 .…”
Section: Step 4: Know the Current Cardiovascular Therapies To Focus O...mentioning
confidence: 99%